Men in canoes navigating flood in Dawson, Yukon Territory, ca. 1897. - La Roche, Frank (1892)
Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number